Gas exchange, phisiological indexes and ionic accumulation in Annona emarginata (Schltdl.) H. Rainer seedlings in nutrients solution - Baron, Daniel [UNESP] (2013)
"Araticum-de-terra-fria" (Annona emarginata (Schltdl.) H. Rainer) has been consider a good alternative in rootstock production for the main commercial Annonaceae species. Although this species develops in different soil and climate conditions, there is no understanding by the physiological responses of this species at different nutritional levels. Thus, the objective of this study was to evaluate the influence of different ionic strengths on development of vegetative species known as "Araticum-de-terra-fria". It was evaluated in seedlings grown in different ionic strengths (25% I, 50% I, 75% I and 100% I) of the complete nutrient solution Hoagland and Arnon (1950) nº 2, for 140 days, the following characteristics: Gas Exchange (CO2 assimilation rate, stomatal conductance, internal CO2 concentration, transpiration rate, water use efficiency, Rubisco carboxylation efficiency); Vegetative growth characteristics (diameter, leaf number, dry matter); Physiological Indexes (leaf area ratio, specific leaf area, relative growth rate, net assimilation rate, leaf weight ratio) and Ionic Accumulation (nutrients leaf analysis). Seedlings grown under 50% I showed the highest values of Leaf CO2 assimilation rate, water use efficiency, carboxylation efficiency, growth, relative growth rate, net assimilation rate and ionic accumulation in the total dry matter. So it is concluded that "Araticum-de-terra-fria" seedlings grown under intermediate nutrient concentrations of complete nutrient solution Hoagland and Arnon (1950) nº 2, explored more adequately their physiological potential that justify their adaptation in different nutritional conditions and allow reducing the amount of mineral nutrition of seedlings production.